Autoantibodies in Systemic Lupus Erythematosus Target Mitochondrial RNA - Becker, Yann; Marcoux, Geneviève; Allaeys, Isabelle; Julien, Anne-Sophie; Loignon, Renée-Claude; Benk-Fortin, Hadrien; Rollet-Labelle, Emmanuelle; Rauch, Joyce; Fortin, Paul R.; Boilard, Eric (Frontiers in Immunology, 2019)
The mitochondrion supplies energy to the cell and regulates apoptosis. Unlike other mammalian organelles, mitochondria are formed by binary fission and cannot be directly produced by the cell. They contain numerous copies of a compact circular genome that encodes RNA molecules and proteins involved in mitochondrial oxidative phosphorylation. Whereas mitochondrial DNA (mtDNA) activates the innate immune system if present in the cytosol or the extracellular milieu, it is also the target of circulating autoantibodies in systemic lupus erythematosus (SLE). However, it is not known whether mitochondrial RNA is also recognized by autoantibodies in SLE. In the present study, we evaluated the presence of autoantibodies targeting mitochondrial RNA (AmtRNA) in SLE. We quantified AmtRNA in an inducible model of murine SLE. The AmtRNA were also determined in SLE patients and healthy volunteers. AmtRNA titers were measured in both our induced model of murine SLE and in human SLE, and biostatistical analyses were performed to determine whether the presence and/or levels of AmtRNA were associated with clinical features expressed by SLE patients. Both IgG and IgM classes of AmtRNA were increased in SLE patients (n = 86) compared to healthy controls (n = 30) (p < 0.0001 and p = 0.0493, respectively). AmtRNA IgG levels correlated with anti-mtDNA-IgG titers (rs = 0.54, p < 0.0001) as well as with both IgG and IgM against β-2-glycoprotein I (anti-β2GPI; rs = 0.22, p = 0.05), and AmtRNA-IgG antibodies were present at higher levels when patients were positive for autoantibodies to double-stranded-genomic DNA (p < 0.0001). AmtRNA-IgG were able to specifically discriminate SLE patients from healthy controls, and were negatively associated with plaque formation (p = 0.04) and lupus nephritis (p = 0.03). Conversely, AmtRNA-IgM titers correlated with those of anti-β2GPI-IgM (rs= 0.48, p < 0.0001). AmtRNA-IgM were higher when patients were positive for anticardiolipin antibodies (aCL-IgG: p = 0.01; aCL-IgM: p = 0.002), but AmtRNA-IgM were not associated with any of the clinical manifestations assessed. These findings identify mtRNA as a novel mitochondrial antigen target in SLE, and support the concept that mitochondria may provide an important source of circulating autoantigens in SLE.